Untuk Siapa Reputasi Tim Kreator Konten tribunjogja.com? (For Whom is the Reputation of The tribunjogja.com Content Creator Team for?) - Ana Nadhya Abrar, MES., PhD (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2021)
The position of the content creator team is very important for tribunjogja.com. They have a special position, so that the news manager just “relented” with their news. The question is, how does the tribunjogja.com content creator team place the idealism of journalists? To understand the idealism of the tribunjogja.com content creator team, this research uses a case study research method. Meanwhile, data collection was carried out using two data collection techniques, namely observation of news produced by the content creator team and in-depth interviews with M. Fathoni, editor of tribunjogja.com, who was not related to the content creator team and the leader of the tribunjogja.com content creator team, Mona. Kriesdinar. It turns out that the tribunjogja.com content creator team upholds their position as intellectuals. However, they are aware that tribunjogja.com cannot develop without positioning it as an economic institution. They make various adjustments. In that adjustment, they have a grip on the idealism of journalists: in line with the limits of reporting. From that adjustment was born reputation which raises the question for whom is the reputation.